Prolonged ventricular pause associated with ticagrelor use: A case report - Alaa Rahhal (Wiley, 2021)
Abstract Case We report a case of a 76‐year‐old female who presented with non‐ST elevation myocardial infarction and developed a 22‐second ventricular pause with ticagrelor that did not recur after shifting to clopidogrel. Based on the Naranjo algorithm, the likelihood that our patient's prolonged ventricular pause was due to ticagrelor exposure was probable. Conclusion Ticagrelor use is associated with prolonged ventricular pauses, warranting close monitoring, particularly during the first week of therapy.